Does market competition make a difference in business strategy for listed companies? - Le Thi Thoan; Vo Thi Ngoc Thuy; Tran Thanh Long (Cogent Business & Management, 2024)
This study investigates the relationship between market competition (MC) and business strategy by analyzing data from 562 non-financial companies listed on the Vietnamese stock market between 2010 and 2019. Utilizing the Generalized Method of Moments (GMM), we assess the impact of MC on specific business strategies, namely cost-leadership and differentiation strategies. The research reveals that MC negatively affects the cost-leadership strategy while positively influencing the differentiation strategy. Grounded in the Theory of Contingency and the Theory of Asymmetric Information, these findings deepen our understanding of MC's implications on business strategy. Additionally, the study provides empirical evidence for future research and proposes implications for both enterprises and government regulatory agencies.This study explores the impact of market competition on business strategy within the Vietnamese context. Our findings reveal a significant correlation between market competition and the adoption of differentiation and cost leadership strategies. The results underscore the pivotal role of strategic choices in navigating highly competitive environments.
Keywords: M10; M20; 650; Business strategy; market competition; emerging market